Management of patients with persistent medically unexplained symptoms: a descriptive study - Kate Sitnikova; Rinske Pret-Oskam; Sandra M. A. Dijkstra-Kersten; Stephanie S. Leone; Harm W. J. van Marwijk; Henriëtte E. van der Horst; Johannes C. van der Wouden (BMC Family Practice, 2018)
Abstract Background In 2013 the Dutch guideline for management of medically unexplained symptoms (MUS) was published. The aim of this study is to assess medical care for patients with persistent MUS as recorded in their electronic medical records, to investigate if this is in line with the national guideline for persistent MUS and whether there are changes in care over time. Methods We conducted an observational study of adult primary care patients with MUS. Routinely recorded health care data were extracted from electronic medical records of patients participating in an ongoing randomised controlled trial in 30 general practices in the Netherlands. Data on general practitioners’ (GPs’) management strategies during MUS consultations were collected in a 5-year period for each patient prior. Management strategies were categorised according to the options offered in the Dutch guideline. Changes in management over time were analysed. Results Data were collected from 1035 MUS consultations (77 patients). Beside history-taking, the most frequently used diagnostic strategies were physical examination (24.5%) and additional investigations by the GP (11.1%). Frequently used therapeutic strategies were prescribing medication (24.6%) and providing explanations (11.2%). As MUS symptoms persisted, GPs adjusted medication, discussed progress and scheduled follow-up appointments more frequently. The least frequently used strategies were exploration of all complaint dimensions (i.e. somatic, cognitive, emotional, behavioural and social) (3.5%) and referral to a psychologist (0.5%) or psychiatrist (0.1%). Conclusions Management of Dutch GPs is partly in line with the Dutch guideline. Medication was possibly prescribed more frequently than recommended, whereas exploration of all complaint dimensions, shared problem definition and referral to mental health care were used less.